Synthesis and Characterization of a Cellulose-Based Polymeric Surfactant Towards Applications in Enhanced Oil Recovery - Afolabi, F. (Springer Science and Business Media Deutschland GmbH, 2021)
The oil and gas industry is in constant search for new solutions for recovery and production enhancement. This need is triggered by the huge hydrocarbon reserves left in subsurface reservoirs after the primary and secondary recovery schemes. Polymeric surfactants are a potential candidate because of their multifaceted functionality. Cellulose-based polymeric surfactants provide an additional advantage of being cost-effective and environmental-friendly. However, a major shortfall of existing polymeric surfactants is their limited surface activity which is essential to manipulate capillary forces within porous media for favorable displacement. Based on new insights into polymer physics and cellulose chemistry, this study aims to develop a novel cellulose-based surfactant with improved capability to reduce surface and interfacial tension to new levels of low while maintaining its solution viscosifying functions. Here, cellulose sulfate is selected as a suitable anionic cellulose derivative backbone while dodecyl polyoxyethylene acrylate is chosen as the surfactant macromonomer for the hydrophobic modification. Using microwave-assisted free radical polymerization, a new compound with a unique molecular structure is synthesized. The various functional groups anticipated in the novel amphiphilic cellulose derivative are confirmed by FTIR spectra analysis. SEM micrograph showed interesting features that could be valuable for chemical enhanced oil recovery applications. The authors suggested further characterization and tests to ascertain the potency of the new product. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.